Efektifitas Penggunaan Game Edukasi Wordwall Untuk Meningkatkan Hasil Belajar IPAS Kelas V SDN 060913 Medan Tembung - Marpaung, Maria Magdalena; Darmawati, Darmawati (Peneliti.net, 2025)
The problem discussed in this study is how to improve the learning outcomes of class V students of SDN 060913 Medan Tembung through wordwall educational games. The purpose of this study is to improve the learning outcomes of class V students of SDN 060913 Medan Tembung through wordwall educational games. The subjects of the study were 24 class V students of SDN 060913 Medan Tembung. This type of research is classroom action research. The research procedure consists of 4 stages, namely planning, action, observation, and reflection. The data collection techniques used in this study are: observation and testing. The results of the study showed that in cycle I the classical completeness criteria were 58,3% with an average student learning outcome score of 58,3, increasing in cycle II the classical completeness criteria were 100% with an average student learning outcome score of 83.125. So there is an increase in student learning outcomes from cycle I to cycle II. In cycle II, student learning outcomes have reached the minimum completion criteria (KKM) set, which is 70. So it can be concluded that there is an increase in the average value from cycle I to cycle II by using the wordwall educational game which makes students more enthusiastic and interested in paying attention to learning so that cycle III is not necessary. Based on the results of the research that has been conducted, it can be concluded that the use of the wordwall educational game can increase the average value of the social science learning outcomes of class V students of SDN 060913 Medan Tembung from 72.5 to 83.125.